PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN INFORMASI LABA AKUNTANSI PADA RETURN SAHAM - Waisaka Putra, Ida Bagus Gede; Karya Utama, I Made (E-Jurnal Akuntansi, 2015)
Corporate social responsibility disclosure and accounting profit is important to know information for investors to predict stock returns to be earned. This research was conducted throughout the 2011-2013 year mining company listed on the Indonesia Stock Exchange, samples were selected using purposive sampling method. The data used in this research is secondary data obtained through an intermediary medium that is from the official website of the Stock Exchange. The analysis technique used is multiple linear regression. The results showed that each of the variables of corporate social responsibility on stock returns and a significant positive effect of accounting earnings information has no effect on stock returns. Therefore, companies must be able to consistently and substantially increase social responsibility form done so investors interested in investing.
Keywords: Corporate Social Responsibility Disclosure, Accounting Profit, and Stock Returns.